Benefits and challenges in the use of RE-AIM for evaluation of a national social work staffing program in the veterans health administration - Cornell, Portia Y.; Hua, Cassandra L.; Halladay, Christopher W.; Halaszynski, Jaime; Harmon, Alita; Koget, Jennifer; Silva, Jennifer W. (Frontiers in Health Services, 2023)
Background In the Department of Veterans Affairs (VA) Veterans Health Administration (VHA), social workers embedded in primary care teams address social and emotional needs that are associated with health outcomes. The mission of the National Social Work PACT Staffing Program is to improve access to social work services for rural Veterans by supporting additional social work staffing in VA medical centers serving rural areas. Methods We obtained data from the VA corporate data warehouse on Veterans’ characteristics and health care use from 2016 to 2022 for all Veterans who received primary care at a Veterans Affairs Medical Center (VAMC) or associated clinic that received funding from the program. We evaluated the program according to RE-AIM constructs as follows: Reach [total number of Veterans who engaged with PACT social work and representativeness with regard to race, rural residence, chronic conditions and health behaviors, and hospital and emergency department (ED) use in the previous 12 months]; Effectiveness (impact of the program on key health care use outcomes which include hospitalizations, emergency department visits, and palliative care); Adoption (number of VA medical centers and outpatient clinics serving rural Veterans that have participated in the program, and number and representativeness of sites eligible for program participation that have not yet received funding); Implementation (adherence to standardized note templates), and Maintenance (permanent social work positions created by the program and continued technical support). Results In 2022, the program engaged with 30,982 Veterans, 65% of whom lived in rural areas. The program increased social work encounters, reduce hospital and emergency department use, and increase use of palliative care services among Veterans. Key elements of implementation include proactive outreach to Veterans with high-risk indicators and assessment for social risk factors using standardized, national note templates. In terms of maintenance, the program continues to provide data and technical assistance to 23 sites and has created 171 permanent social work positions. Conclusions and implications The Social Work PACT Staffing Program demonstrates positive outcomes and program sustainment. The RE-AIM framework was a useful tool to evaluate the program, but additional adaption was needed to fit the program’s needs.